A PROJECT-BASED DIGITAL INSTRUCTIONAL MATERIAL FRAMEWORK: A LITERATURE REVIEW TO ENHANCE STUDENT CREATIVE THINKING SKILLS - Henry Eko Hapsanto (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
The skills of current vocational high school graduates are currently out of alignment with the needs of the job market. Creative thinking skills are projected to be widely used by 2030, and their application relies on Project-Based Learning (PjBL). However, implementation is still hindered by inadequate assessment methods and instructional materials. The objective of this study is to review PjBL in relation to improving creative thinking skills while developing a framework for PjBL-based digital instructional materials that teachers can implement in their instruction. This study was conducted as a literature review in the form of a narrative review. The findings indicate that when using PjBL-based digital instructional materials, it is essential to understand the design stages and syntax that must be followed to ensure learning objectives are achieved.